Addressing the gap in preterm resuscitation practices in high-income and low-middle income countries: a multicenter survey of the Asian neonatal network collaboration - Rohsiswatmo, Rinawati; Dewi, Rizalya; Sutantio, Jennie; Amin, Zubair; Youn, Young-Ah; Kim, Sae Yun; Cho, Su Jin; Chang, Yun Sil; Kusuda, Satoshi; Miyake, Fuyu; Isayama, Tetsuya (Frontiers in Pediatrics, 2025)
BackgroundOptimum neonatal resuscitation practices are vital for improving neonatal survival and neurodevelopment outcomes, particularly in extremely preterm infants. However, such practices may vary between high-income countries (HICs) and low-middle-income countries (LMICs). This study aimed to evaluate the resuscitation practices of high-risk infants in a large multi-country sample of healthcare facilities among HICs and LMICs in Asia under the AsianNeo Network.MethodsIn 2021, a customized 6-item online survey on resuscitation practices of infants born at <29 weeks gestation (or birth weight <1,200 g) was sent by the representative of each country's neonatal network to all the Neonatal Intensive Care Units (NICUs) participating in AsianNeo network. At the time of the survey, there were 446 participating hospitals in eight countries: four high-income countries (Japan, Singapore, South Korea, and Taiwan) and four low-middle-income countries (Malaysia, Indonesia, Philippines, and Thailand).ResultsThe study included 446 hospitals, with a response rate of 72.6% (ranging from 62.7% to 100%), with 179 (55.2%) in HICs and 145 (44.7%) in LMICs. Routine attendance of experienced NICU physicians during resuscitations is reported to be higher in HICs than LMICs, both during daytime (79% vs. 40%) and nighttime (62% vs. 23%). The NRP guidelines in each country were varied, with 4 out of 8 countries using indigenously developed guidelines. Equipment availability during resuscitation was also variable; saturation monitors, radiant warmers, and plastic wraps were available in almost all hospitals, whereas oxygen and air blenders, heated humidified gas, and end-tidal CO2 detectors were more available in HICs. The most common device for Positive Pressure Ventilation (PPV) was the T-piece resuscitator (52.3%).ConclusionThe neonatal resuscitation practices for extremely preterm infants, encompassing staff, equipment, and guidelines, exhibited variance between HICs and LMICs in the AsianNeo region. Further enhancements are imperative to narrow this gap and optimize neonatal outcomes.